2011
DOI: 10.2202/1524-5861.1628
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Globalization on Income Distribution Inequality in 60 Countries

Abstract: This paper investigates the impact of globalization on income inequality distribution in 60 developed, transitional, and developing countries. Using Kearney's (2002, 2003 and 2004) data and principal component analysis (PCA), two globalization indices are created. One of these indices is the equally weighted index. The other index is derived from the principal component analysis. The Gini coefficient of a country is regressed on each index, respectively, in all 60 test cases. The main contribution of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 5 publications
3
24
0
3
Order By: Relevance
“…In particular, the KOF index is used as a measure of Globalization, and the Economic Freedom Index of the Fraser Institute is used to measure within country income inequality. Zhou et al (2011) investigate the impact of globalization on income inequality distribution in 60 developed, transitional and developing countries in 2000. It wasrevealedthat globalization can either alleviate or worsen the income inequality, In summary, most of the empirical literature in the past nine yearsevaluated in this study shown that the debate on the impact of modes of globalization, either economic globalization, Political globalization or otherwise is still controversial and inconclusive.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…In particular, the KOF index is used as a measure of Globalization, and the Economic Freedom Index of the Fraser Institute is used to measure within country income inequality. Zhou et al (2011) investigate the impact of globalization on income inequality distribution in 60 developed, transitional and developing countries in 2000. It wasrevealedthat globalization can either alleviate or worsen the income inequality, In summary, most of the empirical literature in the past nine yearsevaluated in this study shown that the debate on the impact of modes of globalization, either economic globalization, Political globalization or otherwise is still controversial and inconclusive.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…PCA is a method to identify patterns in data and then transforming the data into other form to show differences and similarities between the patterns (Jollife, 2002). PCA will analyze observed data table that described by several dependent variables which are inter-correlated and extract the important information into orthogonal variables called principal components or PC (Zhou et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that globalization has both positive and negative effects for inequality. Zhou et al (2011) investigated the impact of globalization on income inequality distribution in 60 developed, transitional and developing countries in 2000. The study showed that globalization can either mitigate or worsen the income inequality.…”
Section: The Income Inequality and Globalizationmentioning
confidence: 99%